Kyiv as Regime City : The Return of Soviet Power after Nazi Occupation - Blackwell, Martin J. (Book collections on Project MUSE., 2016)
Charts the resettlement of the Ukrainian capital after the end of Nazi occupation and the returning Soviet rulers' efforts to retain political legitimacy